Flexible units planning and operational optimization model under large-scale wind power access. Issue 1 (March 2020) - Gou, Jing; Xu, Weiting; Yang, Xinting; Su, Yunche; Jin, Zhibo; Xu, Hao; Li, Huaqiang
Abstract: After large-scale wind power access to the power grid, the requirements of flexibility of power system become higher, and it is necessary to transform the flexibility of the largest proportion of resources, the thermal units. Firstly, a mathematical model of flexibility requirements and supply of power system is established. Secondly, a supply and demand of flexibility matching probability model based on stochastic chance-constrained programming is built (CCP). Then, a flexible resource planning and operation optimization model is proposed aim to minimize the operational cost of the system. After the transformation of the model, it is solved by using the commercial solver CPLEX. Finally, an example is used to verify the validity of the model. The results show that after the transformation the thermal units can promote the consumption of wind power and reduce the total cost of planning and operation.